SGS-LTER 2008 proposal - Shortgrass Steppe Long Term Ecological Research (SGS-LTER), author (Colorado State University. Libraries, 2008)
Twenty five years of intensive study has revealed a Shortgrass Steppe (SGS) ecosystem that is resilient. Despite chronic water stress, periods of severe drought, and intensive grazing by large herbivores, the essential ecological structure and key interactions maintaining the SGS and its services have remained intact. With global change, however, we may see a range of conditions far outside those experienced on the SGS during the last several thousand years. Forecasting how ecosystems will respond to global change depends on mechanistic understanding of ecosystem drivers. The resilient SGS ecosystem, bounded within "natural" variation but interrupted by human influence, may be supplanted by an unfamiliar one, with humans playing a direct role. Research at SGS-LTER aims toward understanding how ecosystem resilience is influenced by interactions of five key drivers: climate, physiography, biotic structure, natural disturbance, and human landuse. The goal of SGS-LTER renewal is to "test the limits" of resilience, function and structure of the SGS, by both continuing our past work, and by experimentally manipulating factors we know from previous work to be important. We consider multiple temporal scales of change, and our combination of long-term monitoring, short and long-term experiments puts us in the position to forecast the impacts of global change on the SGS. Our global change experiments follow two criteria: i) manipulating factors that will most likely change in the future; and ii) selecting ecological attributes and interactions we previously identified either as vulnerable to change or likely to influence multiple other interactions.
Shortgrass Steppe long term ecological research
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Keywords: long term ecological research; Central Plains Experimental Range; Pawnee National Grassland; grassland ecology; shortgrass steppe